Multi-scale mechanical investigation of articular cartilage suffered progressive pseudorheumatoid dysplasia. (October 2020) - Lin, L.J.; Ge, Y.M.; Tian, Y.; Liu, N.; Luo, X.H.; Xue, Y.T.; Xue, Y.Z.B.; Wen, C.Y.; Tang, B.
Abstract: Background: Progressive pseudorheumatoid dysplasia is a rare skeletal dysplasia mainly caused by abnormal autosomal recessive inheritance. Although the main function of cartilage is mechanical support and the characteristics of this disease is the degradation of AC, previous studies on it had been mainly focused on clinical and genetic aspects and the mechanical behavior of the cartilage affected by PPRD is still ambiguous. In this study, we investigate the mechanics and structure of the cartilage suffered disease at multi-scale, from individual chondrocytes to the bulk-scale tissue. Methods: Depth-sensing indenter were employed to investigate the mechanics of cartilage; we performed atomic force microscope nanoindentation to investigate the cell mechanics and scanning electron microscopy were used to explore the structure feature and chemical composition. Findings: The elastic modulus of chondrocytes harvested from cartilage suffered from progressive pseudorheumatoid dysplasia is significantly higher than from normal cartilage, same trend were also found in tissue level. Moreover, denser collagen meshwork and matrix calcification were also observed. Interpretation: The elastic modulus of cartilage should closely related to its denser structure and the calcification, and may potentially be an indicator for clinical diagnosis. The stiffening of chondrocytes during PPRD progression should play a rather important role in its pathogenesis. Highlights: The elastic modulus of pseudorheumatoid dysplasia cartilage was first measured. Viscoelastic deformation was rigorously considered for accurate measurement. Chondrocyte's elastic modulus influenced by pseudorheumatoid dysplasia was reported.